PENGARUH BAURAN PEMASARAN PARIWISATA TERHADAP KEPUTUSAN UNTUK BERKUNJUNG - Henilia Yulita (Jurnal Hospitality dan Pariwisata, 2017)
Based on BPS data regarding "Data tourist arrivals to the archipelago in JakartaTourism Year 2014 - 2015" found that Taman Impian Jaya Ancol (TIJA) with a verysignificant, is the object of the most visited tourist tourists as many as30,966,381pengunjung. This study examines the "unlock the secrets MARKETINGSTRATEGY" ANCOL OUTSTANDING "(Study of Effects of Tourism Marketing Mixagainst Decision of Visitation)". The research method used by the author in thisresearch is quantitative method. This study uses data processing techniques SPSS20.The data analysis technique is looking for a causal effect between the dependentvariable and independent variables. Data analysis was conducted on 104 respondentswho are citizens of the city and outside Jakarta. This research is used by the levelexplanation, and associative research. Associative research is a method / researchform to connect a variable with other variables. RESULTS: ANOVA (F test) was seenthat simultaneous marketing mix variables have a significant effect on the variablebeen shown Decision of the Sig. 0,000 <Alpha 5% (reject Ho and accept Ha).Variable Decision has been a significant influence by having a contribution of 62.9percent in explaining the change in the variable's decision to visit, while theremaining 37.1 percent is explained by other variables outside the model.Keywords: Tourism Marketing Mix, Visitation Decision